2020
DOI: 10.21203/rs.3.rs-38209/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local delivery of USC-derived exosomes harboring ANGPTL3 enhances spinal cord functional recovery after injury by promoting angiogenesis

Abstract: Background: Spinal cord injury is a devastating clinical condition for which there are currently no effective therapeutic options. In the present study, we aim to investigate the effect of an administered injection of exosomes derived human urine stem cell (USC-Exo) embedded in hydrogel could improve the spinal cord functional recovery after injury and the underlying mechanism.Methods: Exosome were isolate from USC and identified by transmission electron Microscopy (TEM) and western blot. Functional assays in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…1,2 Angiogenesis is an important factor that facilitates neuronal regeneration after SCI. 3 In previous studies, biomaterials, [4][5][6] stem cells, 7 exosomes from neural stem cells, 8,9 or extracorporeal shock waves 10 were used to enhance vessel formation and were found to result in functional recovery in in vivo SCI models.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Angiogenesis is an important factor that facilitates neuronal regeneration after SCI. 3 In previous studies, biomaterials, [4][5][6] stem cells, 7 exosomes from neural stem cells, 8,9 or extracorporeal shock waves 10 were used to enhance vessel formation and were found to result in functional recovery in in vivo SCI models.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have attributed the repair potential of MSCs to exosomes secreted by these cells (31). So far, several studies have been performed on the use of exosomes in the regeneration of damaged spinal cord tissue in animal models including bone marrow (32)(33)(34)(35)(36)(37), adipose(38), Wharton Jelly(38), human umbilical cords (39,40), neural (41), pricytes (42), Peripheral Macrophage (43), Human urine (44), Microglia (45), and human umbilical venous endothelial cells(46). Studies have shown the unique neuro regenerative, angiogenic, and antioxidant properties of hPMSCs, which are promising applications for the treatment of SCI (47).…”
Section: Discussionmentioning
confidence: 99%
“…The ingested exosomes can activate the protein kinase A (PKA) signaling path and promote VEGF expression and consequently angiogenesis (Rauch et al, 2009). Human urine stem cell-derived exosomes can pass through the BSCB and transport ANGPTL3 protein to the SCI area, stimulating angiogenesis through the PI3K/AKT signaling pathway, thereby enabling SCI recovery (Cao et al, 2021). MSC-exosomes packed with phosphatase and tensin homologous small interfering RNA (ExoPTEN) can significantly enhance the angiogenesis and axon regeneration in the damaged spinal cord by reducing PTEN expression in the damaged spinal cord area while reducing microglia and astrocyte proliferation, thereby significantly improving the functional recovery of SCI rats (Kim et al, 2018).…”
Section: Exosomes and Exosomal Mirnasmentioning
confidence: 99%